The quality of butter consumed in konya - Suzan Yalçın; O. Cenap Tekinşen; Yusuf Doğruer; Ümit Gürbüz (Eurasian Journal of Veterinary Sciences)
In this research, chemical and microbiological qua/ities of 15 butter samples taken from Konya market were determined. lt was found that microbiological qualities of butter samples were lo w and chemically most of the samples differed from the values of Food Aegulation and Standards.